Analysis of Growth Accounting and Convergence in MENA Countries: Panel Cointegration Approach. (December 2020) - Malik, Mushtaq Ahmad; Masood, Tariq
The objective of this study is to investigate the sources of output growth and their convergence in the Middle East and North African countries over the period 1970–2017. Towards this end, the study employs Levin et al. (2002, Journal of Econometrics, vol. 108, pp. 1–24), Fisher-type (Choi, 2001, Journal of International Money and Finance, vol. 20, pp. 249–272) and Im et al. (2003, Journal of Econometrics, vol. 115, pp. 53–74) panel unit root tests and Pedroni (2004, Econometric Theory, vol. 20, pp. 597–625), Kao (1999, Journal of Econometrics, vol. 90, pp. 1–44) and Johansen–Fisher cointegration tests. After estimating the production function using random effects estimator to obtain the share of physical capital in output, we employed standard growth accounting approach to measure and decompose growth of total output into contributions from growth in physical capital, labour, human capital and total factor productivity (TFP). Further, the study discusses the existence of stochastic and deterministic convergence of real output per worker and its sources (physical capital per worker, human capital and TFP). The statistical results of the article can be summarized as follows: The contribution of physical capital to output growth is found to be positive and higher than the contribution of labour, whereas the contribution of TFP was negative across the region with the exception of Egypt, Morocco, Tunisia and Turkey. However, when the contribution of human capital is netted out, the contribution of TFP becomes negative in all the countries except for Tunisia. In addition, the study found no clear evidence of deterministic convergence in output per worker (but stochastic convergence), human capital and factor productivity. However, the statistical results provide overwhelming evidence for stochastic and deterministic convergence in physical capital per worker. JEL Classification: O4, O40, O47